2017
DOI: 10.1037/ccp0000258
|View full text |Cite
|
Sign up to set email alerts
|

Form and formulation: Examining the distinctiveness of body image constructs in treatment-seeking patients with binge-eating disorder.

Abstract: Objective Body-image disturbance is a core aspect of eating disorders, yet the clinical manifestations of individuals’ weight and shape concerns are complex, vary considerably, and are poorly understood by clinicians and researchers. This study aimed to distinguish different aspects of body-image disturbance – including weight/shape dissatisfaction, weight/shape overvaluation, weight/shape preoccupation, and fear of weight gain – in patients with binge-eating disorder (BED). Examining how each specific body im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 59 publications
6
51
2
1
Order By: Relevance
“…In this case, future network research could model shape and weight overvaluation as a latent variable, indicated by highly central items (e.g., shape overvaluation, weight overvaluation, desiring weight loss; Epskamp, Rhemtulla, & Borsboom, ). At the same time, certain indicators of shape and weight concerns are differentially associated with ED and comorbid symptoms (Lydecker, White, & Grilo, ). Thus, a second future direction is that time‐series data could be used to construct intraindividual networks (e.g., Epskamp, van Borkulo, van der Veen, Servaas, Isvoranu, Riese, & Cramer, accepted pending revision), with shape and weight overvaluation and other shape and weight concerns indicators modeled as observed variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, future network research could model shape and weight overvaluation as a latent variable, indicated by highly central items (e.g., shape overvaluation, weight overvaluation, desiring weight loss; Epskamp, Rhemtulla, & Borsboom, ). At the same time, certain indicators of shape and weight concerns are differentially associated with ED and comorbid symptoms (Lydecker, White, & Grilo, ). Thus, a second future direction is that time‐series data could be used to construct intraindividual networks (e.g., Epskamp, van Borkulo, van der Veen, Servaas, Isvoranu, Riese, & Cramer, accepted pending revision), with shape and weight overvaluation and other shape and weight concerns indicators modeled as observed variables.…”
Section: Discussionmentioning
confidence: 99%
“…A third future direction is to obtain a more nuanced understanding of shape and weight concerns in people with AN and BN. For instance, shape and weight overvaluation, fearing weight gain, and desiring weight loss may have unique relations with other ED symptoms (c.f., Lydecker et al, ). In addition, factor analytic studies of the EDE and EDE‐Q do not often replicate the proposed four‐factor structure (e.g., Byrne, Allen, Lampard, Dove, & Fursland, 2010; Peterson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in body image are part of the diagnostic criteria (American Psychiatric Association, ) for anorexia nervosa (AN) and bulimia nervosa (BN) and are conceptualized to play critical a role in the maintenance of other eating‐disorder (ED) psychopathology such as extreme dietary restriction, binge eating, purging, low weight, and associated eating‐related concerns (Fairburn, ). Understanding distinctions between different body‐image constructs in EDs has long been confused despite centrality to cognitive‐behavioral models (Fairburn, ) and relatively understudied (Lydecker, White, & Grilo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has consistently supported the distinction between dissatisfaction and overvaluation (Grilo et al, ; Wade, Zhu, & Martin, ) and the prognostic importance of overvaluation (Grilo, White, Gueorguieva, Wilson, & Masheb, ). More recently, studies have yielded empirical evidence regarding potential variations in associations between the other EDE‐based specific body‐image constructs and measures of ED psychopathology (Blechart et al, ; Grilo, Ivezaj, Lydecker, & White, in press; Linardon et al, ; Linardon, Fuller‐Tyszkiewicz, de la Piedad Garcia, Messer, & Brennan, ; Lydecker et al, ; Mitchison et al, ) and outcomes (Calugi & Dalle Grave, ). A few recent studies have jointly considered several body‐image constructs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation